Loss of Domestic Poultry Due to Flood and the State of Veterinary Care Services in Flood-Prone Areas of Bangladesh - Ahmed , Soshe; Haque, Tasmin Sharmin; Rahman, Shaziea; Sultana, Mst. Rokeya; Rahman, Mohammad Mahbubur; Islam, Md. Shahidul; Kabir, Aurangazeb; Moni, Mst. Ishrat Zerin; Haque, Md. Hakimul; Khaton, Rashida (International Journal of Poultry Science, 2019)
Background and Objective: Bangladesh is extremely vulnerable to climate change. Poultry flocks maintained by families in Bangladesh can adversely affected by flood. The purpose of this study was to investigate the loss of family poultry flocks due to flood damage as well as veterinary care services given to domestic poultry in Bangladesh. Materials and Methods: total of 1,985 households that maintained poultry flocks were enrolled from forty villages located in four flood-affected districts in Bangladesh. Data were collected from face-to-face interviews, focus group discussions (FGDs) and direct observations. Data were expressed in terms of frequency and analyzed using descriptive statistics to determine significance of differences between groups. A two-sample t-test was used to test the significance of differences in price for poultry sold during the flood period and the rest of the year. Results: Among the study households, around 80% of poultry shelters were damaged due to flooding and 44% of the poultry was lost. The selling price of poultry during the flood fell significantly (p<0.05) compared to the period after the flood. Lack of feed, clean water and shelter for the poultry were major problems encountered by farmers in Bangladesh during the flood period. After the flood, insufficient veterinary care services, disease outbreaks and lack of money to rebuild flocks were prime problems faced by domestic poultry farmers. The rates of vaccination (2-4% for chicken and ducks respectively), adequate treatment (2-3%) and de-worming (2-4%) were all low for domestic poultry. Mostly pharmacists provided the veterinary health care services and few households engaged the services of registered veterinarians for care of poultry. Conclusion: The study provided a basis to define flood-related problems encountered by domestic poultry farmers in Bangladesh and the state of veterinary care services for the domestic poultry sector.